2015
DOI: 10.1093/eurpub/ckv019
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in cardiovascular mortality in Kazakhstan: further evidence for the ‘Russian mortality paradox’?

Abstract: Hazardous alcohol consumption seems to be highest in Kazakhstan's North-Eastern regions, which might be related to different patterns of alcohol consumption among different ethnic groups. However, more detailed analyses are required to corroborate these assumptions. The high overall rates suggest the need for population-based measures, such as increasing taxes on alcohol, in particular spirits such as vodka, and strengthening the capacity of primary health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…Higher consumption of alcohol in men might partly explain the difference in IHD burden between men and women in these countries. [36] , [37] For example, a study in Uzbekistan, showed that males drink six times as much as females and 1 in 9 male drinkers binged. [38] As for tobacco use and physical activity, findings of the 2014 WHO STEPwise approach to surveillance (STEPS) survey indicated that tobacco was of concern in Uzbekistan as 25% of Uzbek men smoke, and 1 in 6 adults was insufficiently active [38] .…”
Section: Discussionmentioning
confidence: 99%
“…Higher consumption of alcohol in men might partly explain the difference in IHD burden between men and women in these countries. [36] , [37] For example, a study in Uzbekistan, showed that males drink six times as much as females and 1 in 9 male drinkers binged. [38] As for tobacco use and physical activity, findings of the 2014 WHO STEPwise approach to surveillance (STEPS) survey indicated that tobacco was of concern in Uzbekistan as 25% of Uzbek men smoke, and 1 in 6 adults was insufficiently active [38] .…”
Section: Discussionmentioning
confidence: 99%
“…The study reported that despite having higher levels of education and socioeconomic status than Kazakhs, ethnic Russians in Kazakhstan appear to have a higher mortality rate than other ethnicities. Destructive lifestyle such as alcohol consumption, heavy smoking, high-fat diet and lack of physical activity, are claimed to be the major contributing factors for the higher mortality rate amongst Russians [ 23 ]. However, the important question, whether there are other contributing factors besides lifestyle warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies worldwide reported geographic differences within countries in macrovascular disease or in cardiovascular mortality in the general population [ 42 49 ], only few studies reported the regional variations among people with type 2 diabetes. The data from the French national mortality registry from 2002 showed that the burden of diabetes-related mortality was higher in the Northeast than in the West of France [ 50 ].…”
Section: Discussionmentioning
confidence: 99%